ONE-STEP PURIFICATION OF TWO SEMI-SYNTHETIC EPICATECHIN ADDUCTS PREPARED FROM AVOCADO PEELS PROCYANIDINS BY CENTRIFUGAL PARTITION CHROMATOGRAPHY AND EVALUATION OF THEIR ANTI-INFLAMMATORY EFFECTS ON ADENOCARCINOMA GASTRIC CELLS INFECTED WITH Helicobacter pylori - Eillen Torres; Apolinaria García; Mario Aranda; Vania Saéz; Felipe Zúñiga; Julio Alarcón; Marcia Avello; Edgar Pastene (Journal of the Chilean Chemical Society, 2019)
Avocado peels were used to extract proanthocyanidins (PACs) as starting material to prepare semi-synthetic derivatives of epicatechin by nucleophilic attack with pyrogallol and resorcinol. One-step isolation of both semi-synthetic derivatives was successfully performed through centrifugal partition chromatography (CPC), and identified by TLC and LC-MS/MS. The effect upon adherence of Helicobacter pylori ATCC 43504 to AGS cells and the subsequent induction of pro-inflammatory IL-8 release was tested for these two semi-synthetic derivatives. Bacterial adherence and IL-8 synthesis was evaluated using AGS cells con-infected with FITC-labeled H. pylori. Concentration of 700 μg/mL of epicatechin-pyrogallol and epicatechin-resorcinol decreased H. pylori adherence to AGS cells to less than 20% and reduced IL-8 production to less than 10%. In conclusion, semi-synthetic adducts prepared from avocado PACs reduce significantly the adherence and IL-8 production in H. pylori-infected AGS cells.